Property crime in London, 1850 - present - Meier, William M. (Palgrave Macmillan, 2011)
"This book examines London's transformation from the mid-Victorian "miracle" of low (and diminishing) crime to its status as a high-crime society at the outset of the twenty-first century. It treats six different types of misdeed--burglary, shopbreaking, shoplifting, confidence schemes, robbery, and drug smuggling--as representative of distinct phases in the evolution of criminal activity and the criminal-justice system in modern Britain. It argues that the growth of lawbreaking must be explained by connecting sensational and mundane offenses alike to their social and economic contexts, with a particular focus on how these contexts (including experience within the penal system) shape criminal decision-making and expanded opportunities for transgression"--